Development and psychometric exploration of a semi-structured clinical interview for Misophonia. (March 2022) - Guetta, Rachel E.; Cassiello-Robbins, Clair; Anand, Deepika; Rosenthal, M. Zachary
Abstract: Misophonia is a newly described disorder associated with significant emotional distress, functional impairment, and a wide range of mental health problems (e.g., mood, anxiety, and personality disorders). Although recent studies have begun to validate self-report measures of misophonia, no psychometrically validated interviews have been developed. To advance a scientific understanding of misophonia, rigorously developed semi-structured interviews are needed as a complementary measurement approach to self-report inventories. Accordingly, the aim of this study was to develop and begin preliminarily validating a semi-structured clinical interview for misophonia. We took an iterative, grassroots approach to item generation and interview development involving key stakeholders (i.e., misophonia sufferers, experts in the field). Initial psychometric analyses from the current sample ( n = 30) evidenced excellent preliminary estimates for internal consistency, convergent, discriminant, and predictive validity. Results from this study provide preliminary support for the Duke Misophonia Interview, and we recommend that this interviewer-rated measure be iteratively developed and refined using larger and more diverse samples. Highlights: No psychometrically validated interviews have been developed for misophonia. We developed the DMI, a semi-structured interview, to assess misophonia in adults. Findings evidenced preliminary estimates for internal reliability and validity. Results provide preliminary support for the DMI in research and clinical settings. The DMI should continue being validated and refined using larger samples.